Jasmonic acid: a key frontier in conferring abiotic stress tolerance in plants - Raza, Ali; Charagh, Sidra; Zahid, Zainab; Mubarik, Muhammad Salman; Javed, Rida; Siddiqui, Manzer H.; Hasanuzzaman, Mirza (Plant cell reports, 2021)
Abiotic stresses are the primary sources of crop losses globally. The identification of key mechanisms deployed and established by plants in response to abiotic stresses is necessary for the maintenance of their growth and persistence. Recent discoveries have revealed that phytohormones or plant growth regulators (PGRs), mainly jasmonic acid (JA), have increased our knowledge of hormonal signaling of plants under stressful environments. Jasmonic acid is involved in various physiological and biochemical processes associated with plant growth and development as well as plant defense mechanism against wounding by pathogen and insect attacks. Recent findings suggest that JA can mediate the effect of abiotic stresses and help plants to acclimatize under unfavorable conditions. As a vital PGR, JA contributes in many signal transduction pathways, i.e., gene network, regulatory protein, signaling intermediates and enzymes, proteins, and other molecules that act to defend cells from the harmful effects of various environmental stresses. However, JA does not work as an independent regulator, but acts in a complex signaling pathway along other PGRs. Further, JA can protect and maintain the integrity of plant cells under several stresses by up-regulating the antioxidant defense. In this review, we have documented the biosynthesis and metabolism of JA and its protective role against different abiotic stresses. Further, JA-mediated antioxidant potential and its crosstalk with other PGRs have also been discussed.